Education (IRE) in State Senior High Schools - Nurlitasari, Amalia; Maemunah, Maemunah (TARBAWY: Indonesian Journal of Islamic Education, 2024)
Teachers' knowledge and skills in conducting item analysis are still relatively low. Teachers still tend to create questions that are in accordance with core competencies and basic competencies without considering the quality of the test. This study aims to see the quality of question items and examples of questions that are feasible and those that are not feasible through the Mid-Semester Assessment (PTS) of class X Islamic Religious Education (PAI) at SMAN in the city of Yogyakarta. This study is a type of quantitative research and uses the JASP Program version 16.0. The results of the study show that Reliability is in the "High" category. The mean p value is highest in the "Medium" category of 56%. The highest D value is in the "Enough" category of 44% and the most distractions are in the "Acceptable" category of 128 out of 200 questions. Through this calculation, the characteristics of feasible and unfeasible questions can be seen.